BitTorrent: extra-locality P2P approach for grid content distribution networks - Mantoro, Teddy; Shoukat Ali, Haroon (ACM, 2009)
Since the advent of peer-to-peer (P2P) services and applications,they have kept on growing in popularity and more and more people are using them as time progresses. Currently P2P traffic occupies a significant fraction of nearly 70% internet traffic. With the traffic demand for P2P applications being the highest, the ISPs are facing problems to handle the traffic and to provide optimum efficiency on internet services. Attempts made by ISPs to control P2P traffic result in degraded download services for the clients on the other hand. This paper compares and contrasts the different methods which are usually employed to control internet traffic due to P2P activities. We show that the external torrent download method, or its extension, the extra-locality torrent download method, are most optimum when it comes to handling internet traffic. These approaches are the most beneficial to the users as well as the ISPs.